Sputum quality affects assessment of airway microbiology in childhood asthma - Taylor SL; Brooks CR; Elms L; Manning SK; Richard A; Burmanje J; Douwes J; Rogers GB (BioMed Central Ltd, 2025)
Background: The analysis of sputum is the principal basis for characterising lower airway microbiology in those with chronic respiratory conditions. For such analysis to be informative, samples that poorly reflect the lower airways must be identified and removed. Our cross-sectional study explored the relationship between the quality of sputum samples and their microbiological content. We further investigated the impact of excluding low quality samples on observed microbiota-disease relationships in childhood asthma. Methods: Induced sputum was collected from children with or without asthma. Sputum quality was assessed according to squamous cell%, cell viability%, detection of sputum plugs, and salivary α-amylase levels. Sputum microbiota was characterised by 16S rRNA amplicon sequencing and qPCR. Results: Of 170 participants, 130 had asthma. Between 19% (32/170) and 29% (53/170) of samples were deemed to be of insufficient quality, depending on the quality criterion applied. Stratification of samples based on any of the sputum quality cut-offs resulted in significant differences in microbiota characteristics (all p < 0.05), with salivary α-amylase the least discriminant between microbiota of acceptable and unacceptable samples. The removal of 53 poor-quality samples based on ≥ 30% squamous cells identified a difference in the sputum microbiota by asthma status (p = 0.017) that was not evident otherwise, including significantly higher levels of Haemophilus and Gemella in asthma samples. Conclusions: Upper airway contamination of induced sputum samples from children is common. Exclusion of samples based on ≥ 30% squamous cells enables identification of asthma-airway microbiology relationships that are otherwise not apparent.
Keywords: Squamous cell; Inflammatory phenotyping; Haemophilus influenzae; Sputum plug; Microbiota